2016
DOI: 10.1016/j.jad.2016.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect forms of childhood maltreatment and nonsuicidal self-injury among clinically-referred children and youth

Abstract: The present study provides evidence that witnessing domestic violence in childhood is an important risk factor for NSSI. Clinical relevance includes implications for clinicians to develop targeted intervention and prevention strategies for NSSI for children who have witnessed domestic violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
3
24
2
Order By: Relevance
“…Shenk, Noll, and Cassarly (2010) examined data on 129 maltreated and 82 non-maltreated adolescent females aged 14-18 years in the Midwest region of the US and found that adolescents who were sexually abused, neglected, or experienced multiple abuses were significantly more likely to report engaging in NSSI. A bourgeoning number of studies have found that children and adolescents exposed to indirect forms of childhood adversities, such as parental addiction or mental health problems or witnessed domestic violence, are at increased risk of engaging in NSSI (Armiento, Hamza, Stewart, & Leschied, 2016). However, some studies have failed to find a significant association between having a history of ACEs, specifically physical abuse and neglect, and NSSI (Auerbach et al, 2014;Glassman et al, 2007).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Shenk, Noll, and Cassarly (2010) examined data on 129 maltreated and 82 non-maltreated adolescent females aged 14-18 years in the Midwest region of the US and found that adolescents who were sexually abused, neglected, or experienced multiple abuses were significantly more likely to report engaging in NSSI. A bourgeoning number of studies have found that children and adolescents exposed to indirect forms of childhood adversities, such as parental addiction or mental health problems or witnessed domestic violence, are at increased risk of engaging in NSSI (Armiento, Hamza, Stewart, & Leschied, 2016). However, some studies have failed to find a significant association between having a history of ACEs, specifically physical abuse and neglect, and NSSI (Auerbach et al, 2014;Glassman et al, 2007).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…For the purposes of this study, those who engaged in self-injurious behavior with the intent to kill themselves were excluded from the analyses since NSSI includes self-injurious behavior with no suicidal intent. A similar method has been used by past studies in measuring NSSI (see e.g., Armiento et al, 2016;Muehlenkamp & Gutierrez, 2004).…”
Section: Outcome Variablementioning
confidence: 99%
“…Detailed description of the interRAI ChYMH including measurements of variables has been provided elsewhere by the authors , in previous publications (Armiento et al, 2016;Stewart and Hirdes, 2015;Stewart et al, 2015aStewart et al, , 2015b, and is also available from interRAI's website at http://www.interrai.org/ child-and-youth-mental-health.html. In brief, the interRAI ChYMH is a comprehensive instrument comprising approximately 400 clinical elements covering various behavioral and mental state indicators, stress and trauma, child maltreatment history, strength and resilience, family and social support, substance use, medication history, diagnostic information, cognitive and executive functioning, health, nutritional status, and a number of scales that can be used for outcome measurement, as well as care planning protocols that can be used to identify areas of imminent concern or risk.…”
Section: Participantsmentioning
confidence: 99%
“…For the purposes of this study, those who engaged in self-injurious behavior with the intent to kill themselves were excluded from the analyses since NSSI includes self-injurious behavior with no suicidal intent. A similar method has been used by past studies in measuring NSSI (e.g., Armiento et al, 2016;Muehlenkamp and Gutierrez, 2004).…”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation